Bill Brandt: Photography and the Printed Page - Martina Droth (British Art Studies, 2020)
This cover collaboration explores the photography of Bill Brandt (1904–1983) from the perspective of the physical print, drawing attention to its material qualities and practical functions. The small sampling presented here captures some of Brandt’s major visual themes, beginning with his socio-political images of wartime Britain through to his more subjective engagement with landscape and art in the post-war decades. This shift is often seen in terms of Brandt’s career path—from photojournalist in the 1930s and 1940s, to art world photographer in the post-war era. Brandt’s stature as an artist came onto assured footing in the 1960s, with exhibitions at the Museum of Modern Art, New York, in 1961 and 1969, and commercial representation by Marlborough Gallery in the 1970s.1 While Brandt began to print to meet these new expectations, he did not abandon the long-standing practices and interests of his early career: his commitment to the reproduction of photographs on the printed page. Newsprint illustrations and bookplates remained his primary expressive channels. Between 1936 and the year of his death, Brandt published at least one photo-book per decade, as well as contributing dozens of photo-essays and hundreds of individual photographs to illustrated magazines.